Do Control Rights and Family Ownership Affect Capital Structure? - Bedi, Ibrahim; Utama, Cynthia Afriani (International Research Journal of Business Studies, 2024)
This study investigates the existence of a dynamic capital structure, the speed of adjustment towards the optimal capital structure, and the influence of control rights and family ownership on the capital structure of Indonesian listed manufacturing firms. Utilizing the difference Generalized Method of Moments (GMM) estimator and the partial adjustment model on a sample of 60 Indonesian firms from 2014 to 2022, this research provides new insights specific to the Indonesian market. The results confirm the existence of dynamic capital structure and indicate that it takes approximately 1.92 years for manufacturing firms in Indonesia to achieve their target leverage. The results of this study are also consistent with the pecking order theory and the market timing theory. Notably, Controlling Shareholder’s Interest is found to have a positive relationship with leverage. The presence of Family Ownership, however, weakens the relationship between Controlling Shareholders’ Interest and Leverage.